PENGARUH PERILAKU MENGGOSOK GIGI TERHADAP PLAK GIGI DI SD INPRES NIPA-NIPA - Manggarsari, Yayie; Nurwanda, Nurwanda; Jelita, Satria; Alfah, Siti; Ekawati, Nur (Jurnal Ilmiah Amanah Akademika, 2021)
Counseling elementary school students on how to brush their teeth is one of the promotive efforts to improve children's dental and oral health. The aim of this research was to determine the effect of education on how to brush your teeth on the dental plaque index in Inpres Nipa-Nipa Elementary School students. The research was conducted at SD Inpres Nipa-Nipa, using quasi-experimental research methods. The number of samples taken was 50 students with a sampling technique, namely total sampling. This research uses the Wilcoxon statistical analysis test. The results of the study showed that before the education on how to brush your teeth was carried out, the initial plaque index was in the medium category and after the education on how to brush your teeth the final plaque index was in the good category. The results of the Wilcoxon statistical analysis test show p<0.001. The results of this analysis show that there is a significant effect of education on how to brush your teeth on the dental plaque index for students at SD Inpres Nipa-Nipa.